The effect of early radiation in N-body simulations of cosmic structure formation - Adamek, Julian; Rampf, Cornelius (Monthly notices of the Royal Astronomical Society, 2017)
Abstract. Newtonian N-body simulations have been employed successfully over the past decades for the simulation of the cosmological large-scale structure. Such
Gesehen am 22.10.2018